2017
DOI: 10.1021/acs.organomet.6b00913
|View full text |Cite
|
Sign up to set email alerts
|

A Photoswitchable Olefin Metathesis Catalyst

Abstract: A dithienylethene-functionalized N-heterocyclic carbene-Ru(II) complex was synthesized and found to undergo a reversible photoisomerization which influenced its intrinsic catalytic activity. UV-induced ring-closure enhanced the rate of ringclosing metathesis reactions (k closed /k opened = 1.4−1.7) and attenuated the rate of ring-opening metathesis polymerizations (k closed /k opened = 0.56−0.66). Visible light irradiation promoted cycloreversion and restored the initial activity. The ability to switch between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…[47] Recently,t he same group described ap hotoswitchableo lefin metathesis catalyst using a similar NHC ligand. [48] Photochromic and luminescence switching properties of aR e I triscarbonyl complex with dithienylphenanthroline were published by Wing-Wah Yam, Phillips and coworkers. [49,50] However, non-switching coordination complexes with DTE entities werer eported for which no cyclization reaction was observed.…”
Section: Resultsmentioning
confidence: 99%
“…[47] Recently,t he same group described ap hotoswitchableo lefin metathesis catalyst using a similar NHC ligand. [48] Photochromic and luminescence switching properties of aR e I triscarbonyl complex with dithienylphenanthroline were published by Wing-Wah Yam, Phillips and coworkers. [49,50] However, non-switching coordination complexes with DTE entities werer eported for which no cyclization reaction was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Considerably rarer than the switching of a catalytic process between active and inactive states, is switching selectivity between two different pathways . Indeed, within the area of transition‐metal catalysis, only a handful of examples have been reported.…”
Section: Methodsmentioning
confidence: 99%
“…The development of similar ROMP catalysts bearing photochromic chelates (i.e., systems that undergo a reversible light‐mediated transformation) appropriately tethered to the Ru center may also enable switchable polymerizations . For example, we recently reported a photochromic diarylethene (DAE) functionalized Hoveyda‐Grubbs‐type catalyst with two distinct catalytically‐active states that were accessible upon UV ( λ Irr = 313 nm) or visible ( λ Irr > 500 nm) irradiation . As shown in Figure , exposure of a photoswitchable Ru complex equipped with a DAE‐annulated NHC ( 22 ) to UV radiation promoted the reversible electrocyclic photocyclization of the DAE backbone, which attenuated the donating ability of the NHC ligand .…”
Section: Light‐activated Catalystsmentioning
confidence: 99%
“…22 For example, we recently reported a photochromic diarylethene (DAE) functionalized Hoveyda-Grubbs-type catalyst with two distinct catalytically-active states that were accessible upon UV (k Irr 5 313 nm) or visible (k Irr > 500 nm) irradiation. 66 As shown in Figure 10, exposure of a photoswitchable Ru complex equipped with a DAEannulated NHC (22) to UV radiation promoted the reversible electrocyclic photocyclization of the DAE backbone, which attenuated the donating ability of the NHC ligand. 67,68 Moreover, a combination of NMR and UV-vis spectroscopy indicated that 22 cleanly underwent photoisomerization to generate 23 in high conversion.…”
Section: Figurementioning
confidence: 99%